1988
DOI: 10.1037/0003-066x.43.10.755
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of inaction: Psychological factors inhibiting arms control activism.

Abstract: Studies consistently indicate that the American public strongly opposes many aspects of current nuclear arms policy. However, despite this strong sentiment, only a small number of individuals are actively involved in opposing nuclear policies. Explanations of this lack of behavioral response that emphasize public apathy fail to account for prior instances of widespread public involvement in the area o farms control (e.g., the successful protest over atmospheric testing and the massive nuclear freeze rallies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Those who share identical antinuclear attitudes, but do not see the problem as salient, are much less likely to manifest attitude-consistent (antinuclear) behaviors. Gilbert (1988), too, suggested that lack of salience is an important factor in the attenuated relation between antinuclear attitudes and behaviors consistent with such attitude^.^ In part, he attributed the lack of attitude-behavior consistency in this area to "inhibitory effects resulting from the absence of stimuli in the immediate experience of most individuals that could bring the nuclear threat to the center of awareness" (Gilbert, 1988, p. 759). Nonsalience attenuates vested interest and weakens attitude-behavior consistency.…”
Section: Saliencementioning
confidence: 97%
“…Those who share identical antinuclear attitudes, but do not see the problem as salient, are much less likely to manifest attitude-consistent (antinuclear) behaviors. Gilbert (1988), too, suggested that lack of salience is an important factor in the attenuated relation between antinuclear attitudes and behaviors consistent with such attitude^.^ In part, he attributed the lack of attitude-behavior consistency in this area to "inhibitory effects resulting from the absence of stimuli in the immediate experience of most individuals that could bring the nuclear threat to the center of awareness" (Gilbert, 1988, p. 759). Nonsalience attenuates vested interest and weakens attitude-behavior consistency.…”
Section: Saliencementioning
confidence: 97%
“…For example, Gilbert (1988) observed that nuclear arms control activists in the United States were often accused of lack of support for American interests. He argued that the main reason why individuals do not oppose nuclear arms policies is that they would have to defend their commitment to the national interest.…”
Section: Intergroup Conflicts Generally Involve Conflicts Of Interestmentioning
confidence: 99%
“…One important ingredient for accomplishing change is a sense of self-efficacy or a feeling that something can be done (Bandura, 1989). For example, one possible reason for the failure of antinuclear activism in America to achieve wholesale change is the widespread conception that the problem is so big it is pointless to try (Gilbert, 1988;Wolf, Gregory, & Stephan, 1986). Conversely, Edwards and Oskamp (1992) found that peace workers who were most active in the antinuclear war movement had high levels of personal and group efficacy.…”
Section: Increasing Knowledge For Deliberative Participationmentioning
confidence: 99%